GOOD GOVERNANCE IN PAKISTAN: CHALLENGES AND RECOMMENDATIONS - Muhammad Imran; Rohaida Nordin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Good governance is necessary for human development and poverty elimination as it forms a well-functioning public sector that follows the standards of transparency, participation, ownership and accountability to civilians. It forms the transparent and accountable administration of public resources that decrease corruption and ensure that public resources are utilised for the benefit of all citizens in recognition of their fundamental rights. Good governance facilitates an understanding of civil, cultural, economic, social and political rights while holding leaders to account. Hence, good governance and human development are interlinked. This paper defines the concept of good governance. It illustrates the elements necessary for good governance and identifies the problems of good governance in Pakistan. This paper demonstrates that bad governance in Pakistan has created lawlessness, social, economic and political failure. This paper concludes with suggestions to overcome the problems of bad governance in Pakistan.